Diffusion trajectories of emerging sciences in Malaysian R&D system - Wong, Chan-Yuan; Thirucelvam, K.; Ratnavelu, K. (Elsevier, 2010)
In the last two decades, Malaysia has demonstrated significant economic progress and achieved an impressive growth performance in manufacturing exports as a result of its industrial development policies. In order to achieve higher-value-added sector, Research and Development (R&D) activities are necessary. Since the introduction of the first national science and technology policy (1986-1987) and Industrial Technology Development: a National Plan of Action (1990-2001), the Malaysian government has been committed to develop and building up competencies in learning to advance its R&D activities. This paper aims to analyze the trend of scientific production in Malaysia to indicate some characteristics of its R&D system. Logistic growth function is developed to model the growth trajectories of the selected sciences. A time-series of projection of selected technologies is made through logistic curves. In addition, Thailand and Singapore (a country with advanced diffusion of sciences), are included for comparison. (C) 2010 Elsevier Inc. All rights reserved.